1971
DOI: 10.1139/v71-613
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Solvent Isotope Effect for the Spontaneous Solvolysis Acetic and Propionic Anhydrides

Abstract: The large kinetic solvent isotope effects for the neutral hydrolysis of acetic and propionic anhydride show unusual temperature dependency; the former passing through a maximum at about ISo, the latter showing a minimum at 30". This unusual temperature dependency is the consequence of widely different values of the apparent ACp* in H 2 0 and D 2 0 : the value for acetic anhydride in H,O being -74 f 2 cal deg-' mol-' but -32 + 4 in D 2 0 . The corresponding values for propionic anhydride being -31 + 2 in H 2 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

1972
1972
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 15 publications
(17 reference statements)
2
19
1
Order By: Relevance
“…In the case of S-Cl scission, the entropy of activation is negative, as reported for the hydrolysis of sulfonyl chlorides (15)(16)(17). Though the greater solvation of the incipient chloride ion, compared with the aryloxide ion, in the transition state will tend to lead to a more negative AS* in the former case, it appears unlikely that such differential solvation would account for a difference in AS* of about 20 e.u.…”
Section: Discussionmentioning
confidence: 71%
“…In the case of S-Cl scission, the entropy of activation is negative, as reported for the hydrolysis of sulfonyl chlorides (15)(16)(17). Though the greater solvation of the incipient chloride ion, compared with the aryloxide ion, in the transition state will tend to lead to a more negative AS* in the former case, it appears unlikely that such differential solvation would account for a difference in AS* of about 20 e.u.…”
Section: Discussionmentioning
confidence: 71%
“…If K, was estimated to within + lo%, then the error introduced into k0 was less than 0.1%. For the cyclic anhydrides which produced dicarboxylic acids the effective ionic concentration was estimated by using the K, (1) values, hereto, tests indicated this approximation produced no significant error in kO.…”
Section: R + Amentioning
confidence: 99%
“…Water and D 2 0 were purified by methods re~orted previously (1). In all experiments the % D exceeded 99.7Z D. ~i r ; t order rate constants for the reaction of each substrate in H 2 0 and D 2 0 were determined over the widest conveniently attainable temperature range by the conductance method used in the previous study ( I ) and treatment of the temperature dependence of these rates and derivation of pseudo-thermodynamic parameters followed previous formalism.…”
Section: Introductionmentioning
confidence: 99%
“…Some time ago Rossall and Robertson (1) reported that the substitution of a y -M e 0 group in benzenesulfonyl chloride resulted in a more positive temperature coefficient of the enthalpy of activation (AC,') of the solvolysis reaction in water than would be expected from other data (2). This positive shift in AC,* was attributed to a temperature dependent solvation effect, a rationalization supported by reference to corresponding effects found for ACPao for the aqueous ionization of anisic acid (3,4).…”
Section: Introductionmentioning
confidence: 96%